Tales from the haunted South - Korstanje, Maximiliano Emanuel (PASOS Revista de Turismo y Patrimonio Cultural, 2018)
In earlier studies, we have alerted on the lifestyle changes towards a new society. The risk society as it was imagined by postmodern sociologists sets the pace to a new stage of production and capitalism, where death is commoditized to revitalize the psychological frustrations daily happened in working places. The others` death acts as a catalyst giving to a global audience a sentiment of happiness, which is structured in performed rituals. This tendency, which is not limited to tourism industry, can be observed in journalism, press, cultural entertainment and so forth. In a Darwinist world where only the strongest super hero survives, death is conceived as a sign of weakness. This suggests that Thana-capitalism rests on two main pillars, the needs of being special and the prone to be protected. Capitalism structures by the articulation of an extensive exploitation climate where few monopolizes the produced wealth, while the rest lives with nothing. At the time, this untrammeled exploitation expands wasting bodies should be casted as a spectacle to reinforce the center-periphery dependence